An experimental and computational study of the inferior vena cava hemodynamics under respiratory-induced collapse of the infrarenal IVC. (April 2018) - Tedaldi, Elisabetta; Montanari, Chiara; Aycock, Kenneth I.; Sturla, Francesco; Redaelli, Alberto; Manning, Keefe B.
Highlights: Particle image velocimetry experiments and numerical simulations predict that different levels of inferior vena cava (IVC) collapse that occur physiologically during normal breathing and Valsalva influence IVC hemodynamics. A high degree of IVC collapse (50%) generates large WSS (i.e. 5–10 Pa) that have been shown to initiate thrombus formation and platelet deposition in vitro studies. Furthermore, computational simulations points out that IVC hemodynamics are sensitive to small variations in the iliac vein flow splitting. From a clinical perspective, the results could further elucidate the respiratory-induced IVC hemodynamic changes and the occurrence of IVC filter tilt and migration, and potentially contribute to the determination of the optimal IVC filter design and robust criteria for its positioning. Abstract: Inferior vena cava (IVC) filters have been used for over five decades as an alternative to anticoagulation therapy in the treatment of venous thromboembolic disease. However, complications associated with IVC filters remain common. Though many studies have investigated blood flow in the IVC, the effects of respiration-induced IVC collapse have not been evaluated. Our hypothesis is that IVC collapse may have an influence on IVC filter performance. Therefore, we herein investigate the hemodynamics in uncollapsed and collapsed IVC configurations using in vitro flow experiments and computational simulations. Particle image velocimetry (PIV) is used to measure the hemodynamics in an idealized, compliant model of the human IVC made of silicone rubber. Flow is studied under uncollapsed and collapsed scenarios, with the minor diameter of the IVC reduced by 30% in the collapsed state. Both rest and exercise flow conditions are investigated, corresponding to suprarenal flow rates of 2 lpm and 5.5 lpm, respectively. Finite element analysis simulations are carried out in a computational model of the undeformed, idealized IVC to reproduce the 30% collapse configuration and an additional 50% collapse configuration. Computational fluid dynamics (CFD) simulations are then performed to predict the flow in the uncollapsed and collapsed scenarios, and CFD results are compared to the experimental data. The results show that the collapsed states generate a higher velocity jet at the iliac junction that propagates farther into the lumen of the vena cava in comparison to the jet generated in the uncollapsed state. Moreover, 50% collapse of the IVC causes a shift of the jet away from the IVC wall and towards the center of the vena cava lumen. The area of maximum wall shear stress occurs where the jet impacts the wall and is larger in the collapsed scenarios. Secondary flow is also more complex in the collapsed scenarios. Interestingly, this study demonstrates that a small variation in the flow rate distribution between the right and left iliac veins induces significant variations in the flow characteristics. We speculate that asymmetries in the flow may generate unbalanced forces on the IVC wall and on placed IVC filters that could promote filter tilting and migration, although this requires further investigation. If unbalanced forces are present in vivo, the forces should be considered when determining the optimal placement positions and geometric features for IVC filters. Therefore, these findings motivate further investigation of the in vivo hemodynamics in the infrarenal IVC.